Analytical Study of the Results of the Iraqi Volleyball Applicants from Sitting for the Year 2017 - Flayyih, Muhammad Salih; Ulsattar, Maher Abd Ulelah Abd (International Journal of Psychosocial Rehabilitation, 2020)
The search included the introduction and the importance of the search, which is the analysis of the results of the search sample teams and the relationship in the difference order of the teams and the players in order to know the level of difference in Subsequent tournaments and knowledge of the strengths of their investment and focus on them is what the researchers are a problem to be taken care of The descriptive method was used to find the aims of the research: • Identify the results of the teams participating in the Republican Championship in the volleyball of sitting men for the season 2017. • Identify the ratio of the results of the works with the arrangement of the teams participating in the Republican Championship in the volleyball from sitting to the season 2017. Hypothesis There is a statistical ratio between the result of the halfs with the arrangement of the teams participating in the Republican Championship in the volleyball of sitting for the season 2017 It also contained a presentation, analysis and discussion of the results of the orders, their relationship with the ranking of the tournament and the results showed that there was a ratio between the result of the orders and the difference order of the The researchers came out with the following conclusions: • There is a fluctuating in the results of the ships in the teams participating in the Republican Championship in the volleyball from sitting to the season 2017. • Weakness of the formative side of some of the players at the Republican Championship in the volleyball of sitting for the season 2017. • Double side tactic to ask team teams to apply offensive skills to get the